The analysis on work motivation at restaurant as culinary destination in kerawang city west java on covid-19 pandemic - Koerniawaty, Francisca Titing; Wibowo, Valentino Ardian Wahyu (Journal of Business on Hospitality and Tourism, 2022)
COVID-19 pandemic has severely affected for tourism and hospitality businesses globally which caused the transformative on that business particularly the management business, in turn, was the Human Resources Management.  The phenomenon was interesting to be studied for providing essential concept of human resources management.  The purpose of this study was to analyze the employee motivation and its impact on work performance during the pandemic at Bakmi Kota Lama 1819 KIIC Restaurant in Karawang City of West Java Province. This qualitative study was collecting the data by implementing the techniques approach of participative observation by visiting the restaurant as a visitor. The informants were the owner, chef, cook helper, drink section personnel, and waiter or waitress.  The results indicated that the management struggled to provide of the regional standard of minimum wages for the employees. The employees still maintained good motivation to show the productive performance in terms of pandemic survival. The management also has determined to reduce the number of employees by rescheduling the employees to work three times a week.  This caused a little complaint from the employees since there was extra workload due to double job.